Revisiting Tradition-Religion Relationship in Javanese Tayub Dance: How Local Community Deals with Dilemmas - Devita Wulandari; Okta Hadi Nurcahyono; Abdul Rahman (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2021)
Tayub is one of the traditional arts in Indonesia that is still preserved until today. This dance art, for example, is practiced by the Indonesian Islamic Da'wah Institute (LDII) community. Tayub, usually held once a year, is believed to have high values, although many people perceive it negatively. This study aims to reveal why the local religious community still maintains and practices Tayub dance art. The study employs a qualitative approach with a case study on Tayub dance art practiced by the LDII community in Sukoharjo. Data for this study were collected from observations, interviews, and documentation. The study reveals that the socio-religious traditional art practiced by the LDII community brings the community into a dilemma; they should live by either following traditions or carrying out religious tenets. The LDII community continues to maintain and practice the Tayub dance art as an expression of their gratitude. The local community believes that there are noble values contained in Tayub dance art, such as gratitude for God's grace, friendship, and harmony in society. However, many still view this art as a tradition that is not in accordance with religious tenets.